The Drosophila segmentation gene runt has an extended cis-regulatory region that is required for vital expression at other stages of development. - Butler, B.A.; Soong, J.; Gergen, J.P. (Mechanisms of Development, 1992)
The Drosophila runt gene functions in several developmental pathways during embryogenesis. This gene was initially characterized due to the pivotal role that it plays in the genetic regulatory network that establishes the segmented body pattern. Recently it was found that this X-chromosome-linked gene is one of several dosage-sensitive, X-linked components that is involved in activating the Sex-lethal gene in blastoderm stage female embryos. Finally, this gene is also extensively re-expressed in later stages of embryogenesis in the developing nervous system where it plays an important role in the development of specific neural lineages. We have initiated an analysis of the runt cis-regulatory region in order to investigate runt's roles in these (and other) developmental pathways. Analysis of both the function and the expression patterns of runt genes with truncated cis-regulatory regions indicates that there are multiple elements that make quantitative contributions to runt regulation during segmentation. We find that sequences that are more than 8.5 kb upstream of the runt promoter are necessary for normal expression during the post-blastoderm stages of embryogenesis. Genetic experiments indicate that the post-blastoderm expression of runt is vital to the organism.